Оптимизация конструкции роторной головки в модуле "Анализ напряжений" Autodesk Inventor - Гейчук, Владимир Николаевич (НТУ "ХПИ", 2015)
Предложена методика оптимизации конструкции узлов по критерию прочности в CAD/CAE системах со встроенными модулями расчета методом конечных элементов с учетом их функциональных ограничений, в частности в Autodesk Inventor. Выполнена оптимизация конструкции роторной головки для магнитно-абразивной обработки в магнитной системе типа "кольцевая ванна". Критерием оптимизации служил коэффициент запаса прочности, одним из основных ограничений–угол наклона рабочего шпинделя в диапазоне 0-60 градусов.

The method of optimizing the design of the nodes on the criterion of strength in the CAD/CAE systems with built-in finite element analysis based on their functional limitations, particularly in Autodesk Inventor. The instrument of the parametric researches which have been built-in to Au-todesk Inventor, is used in a designed technique at simulation of the is intense-deformed condition of a construction. Recommendations for selection of contact pairs of standard contacts and joints are developed. Also provided are some practical tips for creating the configuration parameters of the model. Some of these include the establishment of relations between the components of the assembly. The optimization of the design of rotary head for magneto-abrasive treatment in the magnetic system of "bathtub ring". Optimization criterion served as a safety factor, one of the main constraints-the working angle of the spindle in the range of 0-60 degrees.
Optimizing the design of a rotary head in the module "STRESS ANALYSIS" AUTODESK INVENTOR
Keywords: магнитно-абразивная обработка; кольцевая ванна; оптимизация; запас прочности; magnetic abrasive machining; circular bath; design; voltage optimization; safety factor